2020
DOI: 10.1523/eneuro.0517-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Does Birth Trigger Cell Death in the Developing Brain?

Abstract: Visual AbstractDevelopmental cell death eliminates half of the neurons initially generated in the mammalian brain, and occurs perinatally in many species. It is possible that the timing of neuronal cell death is developmentally programmed, and only coincidentally associated with birth. Alternatively, birth may play a role in shaping cell Significance StatementThe importance of neuronal cell death for brain development has been recognized for decades, but it is unknown what regulates its timing, or accounts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Term-born mouse pups in the first postnatal week are commonly compared to preterm newborns, based on cortical development milestones (52,99). While direct comparison between developmental stages of mice and humans is difficult due to different rates of maturation, our results confirm previous findings of accelerated brain maturation after premature birth (73,94). Our results further highlight the utility of simple EEG measures in the clinical setting and set the stage for future longitudinal studies that will explore the relationship between 1/f slope and neurodevelopmental outcomes in the preterm population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Term-born mouse pups in the first postnatal week are commonly compared to preterm newborns, based on cortical development milestones (52,99). While direct comparison between developmental stages of mice and humans is difficult due to different rates of maturation, our results confirm previous findings of accelerated brain maturation after premature birth (73,94). Our results further highlight the utility of simple EEG measures in the clinical setting and set the stage for future longitudinal studies that will explore the relationship between 1/f slope and neurodevelopmental outcomes in the preterm population.…”
Section: Discussionsupporting
confidence: 90%
“…While hypoxia represents a severe injury, it may not recapitulate the effects of preterm birth alone. Birth itself is an environmental shock that can significantly affect neuronal and synaptic development (73,94). As the effects of preterm birth in the absence of other pathologies are unclear, our results highlight a need for multiple animal models to capture the variability in the degree of preterm birth-related brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, we isolated the fetal brain 24 h after exposure to hypoxia and normoxia (at E18.5). We elected to use animals that had not been born yet to avoid any confounding effects of early birth on neuronal cell death [63]. A neuropathologist (A.N.V.)…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, premature birth leads to advanced neuronal cell death if cell death rates are compared as a function of post-conception age. Conversely, a delayed birth does not delay the rate of programmed cell death [135]. It is therefore suggested that programmed cell death follows an intrinsic developmental program that can be accelerated by an advanced birth.…”
Section: Control Of Apoptosismentioning
confidence: 99%